To the Question on the Nature of Military Threats and Non-Military Responses - S. R. Tsyrendorzhjyev (MGIMO University Press, 2015)
The notion of "military danger, military threats, military and non-military measures to Parry, and other definitions from the policy of the State to ensure the military security of the now widely used in journalism, conceptual, other documents and research. The attentive reader it is not difficult to notice the ambiguity in the interpretation of these concepts. This makes it difficult to not only the perception of the relevant topics for ensuring military security publications, but also the development of the theory and practice of ensuring the defence and security of the State. The author's view on the essence of the reasoning logic of non-military measures to counter military threats, as the ultimate goal of the article is the following.First the task of analyzing the concept of "national security", "object of national security" and understand the functions of the State, society and the individual to ensure national security. Decomposition of an object of national security, which is "national property" (the content of the concepts described in the article) has made it possible to substantiate the basis for classification of national security threats and with better understanding of the nature, variety, Genesis. This provided a rationale for the role and the place of the tasks ensuring military security in the common task of ensuring national security, the correlation of military and non-military threats.The final phase of the research, the results of which are set out in the article is devoted to analysis of military threats, which made it possible to identify their main structural elements: source, media, military-political and strategic nature, install the main factors defining the content of these elements and their interaction. Based on these results, the proposed definition of the essence of non-military measures for counteracting of military threats, as well as guidelines for developing these measures.